Security risk analysis of bring your own device system in manufacturing company at Tangerang - Astari Retnowardhani; Raziv Herman Diputra; Yaya Sudarya Triana (Universitas Ahmad Dahlan, 2019)
Nowadays information system has become popular used for help effectiveness and efficiency operation on a company. Bring Your Own Device (BYOD) system is a growing trend in corporate environment, where employees could access the system from anywhere. BYOD system is system information development using some technology like a Virtual Private Networks (VPN) or using some application to make the client on outside network office can access to inside networks with remote system. The remote system has strength to help employees working anywhere and anytime, that could make some issue for a security thing. The security issue that can be happen is unauthorized access and lost some important of company information. XYZ company as a manufacturing company in Tangerang, Indonesia has been used BYOD system in their company. They want to improve the security of the system with do risk analysis, with the aim to protect the internal data. The risk analysis use Cybersecurity Framework NIST will assist organizations to understand the risk of BYOD system. The analysist results obtained by the use of cybersecurity analysis on BYOD system in XYZ company are found some improvement need to develop in terms of security system recommended. According to the stages of respond with the analysis using Cybersecurity NIST framework and ISO/IEC 27002:2013.